Kisan Choupal Promoting better reach and acceptance - Aditya, Aditya; Mankar, Abhay; Sohane, R. K. (Indian Farming, 2015)
Kisan Chaupal is leaving indelible footmarks in the way extension activity needs to be practiced to reach the farmers efficiently. The initiative has facilitated better reach and access to the modern technologies in farming. Also, it has enabled to build better rapport of the scientists among the farmers which have helped the Krishi Vigyan Kendra's and agricultural colleges of the farmers  to get their problems on cropping resolved immediately. The university has also provided better support to the farmers in the form of quality planting material, seeds etc. to maintain the interest of the farmers and be of need at all times to make agriculture a better  option for the farming community and the youth.